2002
DOI: 10.1046/j.1471-4159.2002.01118.x
|View full text |Cite
|
Sign up to set email alerts
|

Lack of up‐regulation of ferritin is associated with sustained iron regulatory protein‐1 binding activity in the substantia nigra of patients with Parkinson's disease

Abstract: Dopaminergic neurones degenerate during Parkinson's disease and cell loss is most extensive in the subpopulation of melanized neurones located in the substantia nigra pars compacta. Iron accumulation, together with a lack of up-regulation of the iron-storing protein, ferritin, has been reported and may contribute to increased oxidative stress in this region. We investigated the binding activity of iron regulatory protein-1 (IRP1) to the iron-responsive element that precludes ferritin mRNA translation, in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(72 citation statements)
references
References 50 publications
(49 reference statements)
4
67
0
1
Order By: Relevance
“…Increased iron concentrations and oxidative damage have been observed in damaged regions of the substantia nigra in both human cases of Parkinson's disease (PD) and in animal models [29,30]. Taken together with rotenone-induced experimental models of Parkinson's disease [22], we hypothesized that rotenone may increase levels of ferritin H. In fact, we observed that ferritin H is induced following rotenone exposure at the mRNA and protein synthesis levels in NIH3T3 fibroblasts and SH-SY5Y neuroblastoma cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Increased iron concentrations and oxidative damage have been observed in damaged regions of the substantia nigra in both human cases of Parkinson's disease (PD) and in animal models [29,30]. Taken together with rotenone-induced experimental models of Parkinson's disease [22], we hypothesized that rotenone may increase levels of ferritin H. In fact, we observed that ferritin H is induced following rotenone exposure at the mRNA and protein synthesis levels in NIH3T3 fibroblasts and SH-SY5Y neuroblastoma cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Iron deficiency during development alters the course of neurobehavioral development (Erikson et al, 2000;2001;Piñ ero et al, 2001;Beard et al, 2002; and iron deficiency in late adulthood has been implicated in movement disorders and neuroleptic malignant syndrome (Lee, 1998;Allen et al, 2001). Moreover, iron overload in adulthood has been shown to participate in neurodegenerative disorders (Faucheux et al, 2002;Sipe et al, 2002) and diseases of excess iron in tissues, for example, hemochromatosis have associated neurological and psychiatric disorders (Cutler, 1994;Feifel and Young, 1997). It is evident therefore that proper iron regulation is critical for normal CNS development and functioning.…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis of an increase of iron in the SN of patients is generally accepted and documented (Sofic et al 1988;Dexter et al 1989;Oakley et al 2007), even though the difference between controls and PD samples appears to be affected by factors such as disease severity, gender or age of onset (Snyder and Connor 2009). Less clear are the modification of ferritin levels, with studies showing an increase (Sofic et al 1988;Licker et al 2014), a decrease (Dexter et al 1990;Connor et al 1995;Faucheux et al 2002) or changes in the relative H/L ratio (Koziorowski et al 2007), with consequent functional implication for iron handling. The loss of neurons (rich in H subunit), the reactive gliosis (microglial cells are rich in L ferritin) as well as technical aspects such as the type of antibodies applied for IHC may be important confounding factor in this analysis (Snyder and Connor 2009).…”
Section: Ferritin In Brain Disorders With Altered Iron Homeostasismentioning
confidence: 99%